2022
DOI: 10.3390/ph15111412
|View full text |Cite
|
Sign up to set email alerts
|

IL-17/Notch1/STAT3 Pathway Contributes to 5-Fluorouracil-Induced Intestinal Mucositis in Rats: Amelioration by Thymol Treatment

Abstract: 5-Fluorouracil (5-FU) is an anticancer drug with intestinal mucositis (IM) as a deleterious side effect. Thymol is a monoterpene phenol which has been reported to possess an antioxidant and anti-inflammatory activity versus 5-FU-induced IM. The Notch pathway affects multiple cellular activities, such as cellular proliferation, in addition to inflammatory responses modulation. Accordingly, this work was carried out in order to elucidate the role of the Notch pathway in 5-FU-induced IM and to further elucidate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…5-FU is another commonly used chemotherapeutic agent employed in the therapy of various cancers, which can cause damage to intestinal epithelial cells and result in intestinal mucositis ( 15 , 65 , 66 ). To test the role of LTβR signaling in a 5-FU model of chemotherapy-induced intestinal injury, we treated WT and LTβR -/- mice with 50 mg/kg 5-FU daily for 4 days ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…5-FU is another commonly used chemotherapeutic agent employed in the therapy of various cancers, which can cause damage to intestinal epithelial cells and result in intestinal mucositis ( 15 , 65 , 66 ). To test the role of LTβR signaling in a 5-FU model of chemotherapy-induced intestinal injury, we treated WT and LTβR -/- mice with 50 mg/kg 5-FU daily for 4 days ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, radioprotective effects of thymol and carvacrol have been documented in different ionizing radiation-induced injuries [ 32 , 33 , 34 , 35 , 36 ]. Studies showed that carvacrol and thymol have some promising effects against chemotherapy-induced nephrotoxicity through antioxidative, antiapoptotic, anti-inflammatory, and cytoprotective mechanisms [ 37 , 38 , 39 , 40 ]. Carvacrol has been reported to be a ligand for the transient receptor potential channel ankyrin 1 (TRPA1), which mediates the expression and release of CGRP [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%